2003
DOI: 10.1189/jlb.0703315
|View full text |Cite
|
Sign up to set email alerts
|

Host defense function of the airway epithelium in health and disease: clinical background

Abstract: Respiratory infection is extremely common and a major cause of morbidity and mortality worldwide. The airway epithelium has an important role in host defense against infection and this is illustrated in this review by considering infection by respiratory viruses. In patients with asthma or chronic obstructive pulmonary disease, respiratory viruses are a common trigger of exacerbations. Rhinoviruses (RV) are the most common virus type detected. Knowledge of the immunopathogenesis of such RV-induced exacerbation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
122
1
7

Year Published

2005
2005
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 139 publications
(136 citation statements)
references
References 165 publications
(156 reference statements)
6
122
1
7
Order By: Relevance
“…The mechanisms by which RV infections induce lower respiratory symptoms and alterations in lung physiology in asthma are not well understood (26). However, given that primary bronchial epithelial cells from asthmatic subjects replicate RV efficiently in vitro, whereas those from normal individuals are much more resistant to Peripheral blood CD4 ϩ IFN-␥ and IL-10 production were assessed at baseline before experimental RV infection by intracellular cytokine staining.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which RV infections induce lower respiratory symptoms and alterations in lung physiology in asthma are not well understood (26). However, given that primary bronchial epithelial cells from asthmatic subjects replicate RV efficiently in vitro, whereas those from normal individuals are much more resistant to Peripheral blood CD4 ϩ IFN-␥ and IL-10 production were assessed at baseline before experimental RV infection by intracellular cytokine staining.…”
Section: Discussionmentioning
confidence: 99%
“…IFN-c is known to up-regulate MHC class II gene expression and regulate antigen processing by augmenting the proteolysis and peptide transport machinery in APC [13,14]. Airway epithelial cells are the initial site of respiratory virus infection and have the capacity to produce a variety of biologically active molecules, and involved in inflammation and immune responses [52]. They may act as nonprofessional APC during respiratory viral infections [9].…”
mentioning
confidence: 99%
“…In the case of E. purpurea, all the fractions derived from roots, leaves plus stems, and flowers, were anti-inflammatory according to IL-6 and IL-8 measurements. The cytokine IL-6 is one of the principal pro-inflammatory cytokines, and is considered to be an excellent indicator of inflammatory status (Message & Johnston, 2004;Schaller et al, 2006). The cytokine IL-8 is one of the most important chemokines which attracts neutrophils and other inflammatory cells to sites of infection (Schaller et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Rhinoviruses have been implicated as major players in common colds and various types of allergic rhinitis and bronchial syndromes (Message & Johnston, 2004;Schaller et al, 2006). However, numerous studies have shown that rhinovirus infection in cultured epithelial cells, and in nasal epithelial tissues in vivo, results in relatively low levels of virus replication and cytopathology, apparently due to the small number of cells supporting virus replication (Mosser et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation